2023
DOI: 10.3390/ijms242216410
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Senescence: A Troy Horse in Pulmonary Fibrosis

Ruyan Wan,
Lan Wang,
Miaomiao Zhu
et al.

Abstract: Pulmonary fibrosis (PF) is a chronic interstitial lung disease characterized by myofibroblast abnormal activation and extracellular matrix deposition. However, the pathogenesis of PF remains unclear, and treatment options are limited. Epidemiological studies have shown that the average age of PF patients is estimated to be over 65 years, and the incidence of the disease increases with age. Therefore, PF is considered an age-related disease. A preliminary study on PF patients demonstrated that the combination t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 171 publications
0
7
0
Order By: Relevance
“…Despite the FDA approval of two drugs, pirfenidone and nintedanib, for the treatment of IPF, these medications only moderately slow disease progression and are associated with certain adverse reactions [6,28]. Given the global aging population and cell senescence as a major driving force for tissue and organ aging, there is an urgent need to identify new targets for regulating cellular senescence [29]. In this study, we found that NR2F2 was downregulated in the lung tissue of both IPF patients and bleomycin-induced fibrotic mouse models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the FDA approval of two drugs, pirfenidone and nintedanib, for the treatment of IPF, these medications only moderately slow disease progression and are associated with certain adverse reactions [6,28]. Given the global aging population and cell senescence as a major driving force for tissue and organ aging, there is an urgent need to identify new targets for regulating cellular senescence [29]. In this study, we found that NR2F2 was downregulated in the lung tissue of both IPF patients and bleomycin-induced fibrotic mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found a widespread presence of SASP in various senescent cell populations in the lungs of experimental pulmonary fibrosis models and IPF patients [40][41][42]. These SASP components not only serve as markers of senescence in the lung fibrosis development process but also actively participate in the senescence process and regulate the progression of pulmonary fibrosis [29]. Therefore, we further investigated whether senescent epithelial cells regulated by NR2F2 would express and secrete excessive SASP factors, thereby influencing the activation of lung fibroblasts through paracrine effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Senescent cells secrete a number of cytokines, including proinflammatory cytokine and chemokines, growth regulators, angiogenic factors and matrix metalloproteinase, collectively known as the SASP or the senescence information secretory group. SASP has been recognized as a marker of senescent cells and mediates many pathophysiological effects [198]. In addition, DNA damage, telomere depletion, epigenetic changes, protein damage, lipid damage, dysfunction of mitochondria and lysosomes, ROS and inflammation are all important inducers of cell senescence [199].…”
Section: Main Causes Of Cellular Senescencementioning
confidence: 99%
“…Senescent cells exhibit abnormally high levels of damage accumulation, including DNA damage, telomere dysfunction, mitochondrial dysfunction and ROS accumulation [201]. Elimination of senescent cells reduces the number of cells with the highest degree of damage [191,198]. Therefore, treatment methods that improve or delay cellular senescence characteristics are important strategies for delaying aging.…”
Section: Relationship Between Cellular Senescence and Agingmentioning
confidence: 99%